2014
DOI: 10.1016/j.procbio.2014.01.022
|View full text |Cite
|
Sign up to set email alerts
|

New at-line flow cytometric protocols for determining carotenoid content and cell viability during Rhodosporidium toruloides NCYC 921 batch growth

Abstract: a b s t r a c tRhodosporidium toruloides NCYC 921 batch growth was monitored as a means to evaluate the yeast biomass potential as a source for the production of carotenoids and other lipids.Carotenoid content, cell viability and size were assessed by multiparameter flow cytometry. The saponifiable lipid fraction was assayed by gas-liquid chromatography.The carotenoid production increased during the stationary phase, reaching 78 g/g while the total fatty acid content attained 32% (w/w) at the end of the fermen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…More interestingly, wild-type R. toruloides also produces carotenoids that give colonies a red phenotype. As carotenoids are high value products, co-production of carotenoids may contribute to improve the technoeconomics of microbial lipid technology (Parreira et al 2015;Freitas et al 2014). Indeed, a few attempts have employed Rhodosporidium and related genera for production of carotenoids which are useful as natural food colorants and feed additives in aqua culture (Nasrabadi and Razavi 2011;Ruhiyat et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…More interestingly, wild-type R. toruloides also produces carotenoids that give colonies a red phenotype. As carotenoids are high value products, co-production of carotenoids may contribute to improve the technoeconomics of microbial lipid technology (Parreira et al 2015;Freitas et al 2014). Indeed, a few attempts have employed Rhodosporidium and related genera for production of carotenoids which are useful as natural food colorants and feed additives in aqua culture (Nasrabadi and Razavi 2011;Ruhiyat et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…toruloides CECT 1499 (this study), R. toruloides Y4[13], R. toruloides NCYC 921[67], R. glutinis/S. toruloides CECT 1499 (this study), R. toruloides Y4[13], R. toruloides NCYC 921[67], R. glutinis/S.…”
mentioning
confidence: 77%
“…It has been recommended that FSC and SSC scattering can be potentially used to monitor microbial physiological state. Two different studies reported the physiological state of R. glutinis and R. toruloides using flow cytometry . During the exponential phase of the cultivation, two well‐defined individual peaks were observed in the FSC/SSC plot for R. glutinis , one peak indicating the matured cells and another indicating budding cells while average fluorescent reading of FSC/SSC was increased for R. toruloides but no division in the major peak.…”
Section: Limitations and Hurdles Of Flow Cytometry‐based Methods In Omentioning
confidence: 99%
“…That is, during exponential phase, the budding pattern and proportion of R. glutinis differ from R. toruloides . Therefore, the average and pattern of FSC/SSC signals for exponential phase (of both R. glutinis and R. toruloides ) was a balance between the proportion of budding cells and new small cells . Since it is hard to conclude how a cell can behave at a particular growth phase, it is important to carry out the correct control experiments for each organism analysed.…”
Section: Limitations and Hurdles Of Flow Cytometry‐based Methods In Omentioning
confidence: 99%
See 1 more Smart Citation